Gross Anatomical Study onthe Skull and Mandible ofthe Wild Boar (SusScrofa) In the Caribbean - Reda Mohamed (Academia Anatomica International, 2019)
Introduction:Wild pigs (Susscrofa), which are found throughout the Caribbean island of Trinidad and Tobago, are sometimes used experimentally, in the field of biomedical science, to model the human anatomy. In particular, the skull, which is very important as ithouses vital organs and foramina,has clinical importance in applying regional anesthesia.Subjects and Methods:The present work was conducted on two skulls and mandibles of wild pigsto grossly describe their osteology and foramina. The information garnered can be used for comparative studies of the skulls and mandibles with other similar species. The skulls and mandibles were prepared and cleaned using standard method. All of the characteristic features of various standards views of the skulls bones, including dorsal, lateral, caudal, and the lateral, rostral and caudal views of the mandibles as well as the foramina of the skulls and mandibles were described and discussed.Results:Each skull was divided into long facial and short cranial regions. The tympanic bulla was small. The supraorbital foramina and grooves were present. The zygomatic process of the zygomatic bone and the zygomatic process of the temporal bone formed the large zygomatic arch. The mandible was a paired bone with ossified mandibular symphysis. The dental formula was confirmed and it was 44 teeth.Conclusion:The bones and foramina of the skull and mandible were homologue to that of other mammals.